2003
DOI: 10.1021/es026473i
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Major Sources Contributing to PM2.5Observed in Toronto

Abstract: The chemical composition of Toronto PM2.5 was measured daily from Feb 2000 to Feb 2001, and source apportionment was undertaken using positive matrix factorization (PMF). In Toronto, PM2.5 levels were influenced both by local urban activities and also by regional-scale transport. Although several PMF solutions were possible, an eight-source model for explaining the observed Toronto PM2.5 was found to provide realistic results and interesting insights into sources. The four main sources were coal combustion rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 47 publications
8
119
0
Order By: Relevance
“…At the roof level, the average concentrations of those 12 elements were 2724 (Al), 1908 (Fe), 570.3 (Zn), 212.3 (Pb), 72.19 (Mn), 53.55 (Cu), 25.64 (As), 9.764 (Cr), 6.345 (Ni), 4.732 (Cd), 2.185 (Mo) and 0.816 ng/m 3 (Co). These data are comparable to those reported by Wang et al, (2006) and Duan et al (2006) for Guangzhou and Beijing, but are much higher than major cities around the world where more strict emission standards are applied (Ariola et al, 2006;Lee et al, 2003;Louie et al, 2005;Singh et al, 2002).…”
Section: Trace Metal Analysissupporting
confidence: 84%
“…At the roof level, the average concentrations of those 12 elements were 2724 (Al), 1908 (Fe), 570.3 (Zn), 212.3 (Pb), 72.19 (Mn), 53.55 (Cu), 25.64 (As), 9.764 (Cr), 6.345 (Ni), 4.732 (Cd), 2.185 (Mo) and 0.816 ng/m 3 (Co). These data are comparable to those reported by Wang et al, (2006) and Duan et al (2006) for Guangzhou and Beijing, but are much higher than major cities around the world where more strict emission standards are applied (Ariola et al, 2006;Lee et al, 2003;Louie et al, 2005;Singh et al, 2002).…”
Section: Trace Metal Analysissupporting
confidence: 84%
“…These data have been used for outdoor PM 2.5 source apportionment studies and have been described elsewhere. 9 Pollutants measured included 24-hr. (ϳ8:00 a.m. to 8:00 a.m. EST) PM, carbon, inorganic ions, water-soluble organic substances, and hourly gaseous pollutants, such as CO, nitrogen oxides (NO x ), ozone (O 3 ), and coefficient of haze.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, an eight-source receptor model was constructed to apportion PM 2.5 in Toronto, Ontario, Canada. 9 These included coal combustion related to regional transport and secondary sulfate, secondary nitrate, secondary organic aerosols, motor vehicle traffic, road salt, and three primary PM 2.5 sources associated with smelters: coal and oil combustion, industry, and local construction. In the residential indoor environment, major sources can be cooking, vacuuming, dusting, tobacco smoke, and wood-burning fires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the highest SO 2 concentrations in the COR have been recorded in the vicinity of large local industrial sources. Lee et al 197 found that long-range transport contributes to the SO 4 2Ϫ pollution within the COR.…”
Section: Greater Toronto Area and Central Ontariomentioning
confidence: 99%